Effects of the nature and charge of the topmost layer in layer by layer self assembled amperometric enzyme electrodes - Calvo, Ernesto Julio (2010)
Organized layer-by-layer nanostructured amperometric enzyme electrodes with self-contained redox polyelectrolyte mediators have shown important effects depending on the nature and charge of the adsorbed topmost layer. Adsorption of PVS causes the drop of the catalytic responses to negligible values due to hindrance in electron hopping and enzyme wiring.